Distribution and interactions of priority heavy metals with some antioxidant micronutrients in inhabitants of a lead-zinc mining community of ebonyi state, Nigeria - Bello H Tilako; Sylvester O Ogbodo; Innocent N Okonkwo; Imelda N Nubila; Irene L Shuneba; Enyinna Ogbonna; Saidi Odoma; Rebecca M Gali; Bassey E Bassey; Elvis N Shu (Advances in Toxicology and Toxic Effects - Peertechz Publications, 2020)
Background: Human exposure to xenobiotics, especially priority heavy metals (lead, cadmium, arsenic, mercury and chromium), is unavoidable because of their involvement in industrial applications, accumulation in the environment over time and non-biodegradability. Unfortunately, they induce unprecedented biochemical and pathological changes on those exposed to them, causing oxidative damages and organ toxicities. Aim: This study investigated the frequencies of priority heavy metals and their impact on some micronutrient elements (copper, iron, zinc) in the blood of inhabitants of a lead-zinc mining community in southeastern Nigeria. Methods: Subjects, who were aged between 10 and 60 years, included 89 artisanal miners (occupationally-exposed), 61 non-miners living in the same community (environmentally-exposed) and 65 non-miners from a distant community (controls). Both priority heavy metals and the micronutrient elements were estimated using the atomic absorption spectrophotometric method. Results: Results showed that all the studied priority heavy metals have frequencies higher than the WHO-recommended levels and their concentrations in occupationally-exposed subjects were significantly higher than their concentrations in both environmentally-exposed and control subjects. Likewise, their concentrations in environmentally-exposed subjects were significantly higher than those in the control subjects. It was also observed that the concentrations of the micronutrient elements in occupationally-exposed subjects were significantly lower than their concentrations in both environmentally-exposed and control subjects, showing strong negative correlations between these priority heavy metals and the micronutrient elements. Conclusion: This study indicates that other priority heavy metals other than lead are prevalent in the studied area and these metals affect the absorption and metabolism of micronutrient elements and may also affect the antioxidant activities and other biological functions of the micronutrients.